Koncept för förbättrat mobiliseringsmoment inom sjukvården för kolorektalkirurgi - Hansenäs, Rosanna; Silvander, Karin (My University, 2020)
At Sahlgrenska University Hospital's, east, at ward 351 care is given to patients who have undergone colorectal or rectum cancer, a so-called reconstructed flap surgery. In order for the healing of the patient too go as smoothly as possible and without complications, these patients must be mobilized several times a day. In the ward, many patients are cared for and time is not always enough to carry out the mobilization of patients as much as the personnel wish. This is due to the fact that a larger group of the staff is required to mobilize a single patient. With this as a basis, a product concept was created to make the mobilization more efficient. Today 4-5 of the personnel are required to move patient from their hospital bed to a mobilization aid known as the tipping board. There, the patient is then mobilized by raising the patient from lying down to upright without having the patient bend any part of the body, this is done with the tipping board. When upright, the patient can begin to slowly move around in the room. This procedure was observed, and the staff were interviewed. Furthermore, ideas were generated and presented to the supervisors at the ward. The ideas were then combined through a morphological matrix and evaluated with the help of a PNI. Concepts with greater potential were refined and a functional model was then built to test elevation and lowering functions. Finally, a concept was created that facilitates staff in its daily work with patients who has undergone a reconstructive flap surgery. To visualize and present this concept, a model was created in CATIA V5.